ÐšÑ€Ð¸Ð¾Ð·Ð°Ñ‰Ð¸Ñ‚Ð½Ð°Ñ ÑÑ„Ñ„ÐµÐºÑ‚Ð¸Ð²Ð½Ð¾ÑÑ‚ÑŒ Ñ€ÑÐ´Ð° ÐºÑ€Ð¸Ð¾Ð¿Ñ€Ð¾Ñ‚ÐµÐºÑ‚Ð¾Ñ€Ð¾Ð² Ð² Ð·Ð°Ð²Ð¸ÑÐ¸Ð¼Ð¾ÑÑ‚Ð¸ Ð¾Ñ‚ ÑÐºÐ¾Ñ€Ð¾ÑÑ‚Ð¸ Ð¾Ñ…Ð»Ð°Ð¶Ð´ÐµÐ½Ð¸Ñ - Chernobai, N. A.; Gurina, T. M.; Pakhomov, A. V. (Publishing House ‘Akademperiodyka’ of the National Academy of Sciences of Ukraine; Institute for Problems of Cryobiology and Cryomedicine, 2024)
The survival of testes interstitial cells after freeze-thawing using the cooling rates of 1; 5 and 10 deg/min and glycerol (7%), dimethyl sulfoxide (10%), ethylene glycol (7%) and dimethyl formamide (5%) solutions has been estimated. Using of glycerol provided sufficiently high (up to 75%) cell survival under all the studied cooling rates. Cell survival increased (from 56% upto 83%) if cooling rates were elevated from 1 up to 10 deg/min in the case of other cryoprotectants. Cooling rates about 10 deg/min provided sufficiently high level of post-thaw cell survival.